Dampak Domino pasca krisis Eurozone di ASEAN 5 (Thailand, Filipina, Malaysia, Singapura dan Indonesia) Tahun 2008 - Wira Ganet Aribowo; Arini Wildaniyati (Universitas Merdeka Madiun, 2023)
Abstract— In early 2023 there was an American financial crisis, it’s Silicon Valley Bank and Signature Bank experienced liquidity difficulties, although the context was different and the financial authorities were handling it, but it reminded me of the time when Greece experienced a financial crisis in 2008, many countries were affected by the domino effect to a certain degree. The Greek crisis had an impact on the economic and political stability of the European Union at that time. Contagion's impact was felt in the ASEAN 5 countries (Thailand, Philippines, Malaysia, Singapore and Indonesia) from the Greek financial crisis which also affected the economic and political structure. Therefore it is necessary to evaluate the impact of the crisis on the Indonesian economy to anticipate the possibility of a secondary crisis. Using a descriptive analysis of a quantitative approach, to capture the Domino Effect contagion relationship between GDP, country Debt Ratio, Broad Money and inflation, which occurred during the Greek crisis in 2008 in ASEAN 5 countries (Thailand, Philippines, Malaysia, Singapore and Indonesia) with a time span of 2008 - 2017 The estimation results show that the impact of the Greek crisis will not have a significant impact. This indicates that investors may have realized that the ASEAN 5 economies (Thailand, the Philippines, Malaysia, Singapore and Indonesia) were quite isolated from the Greek crisis and therefore did not change the perception of sovereign risk.